Classifying logistics-relevant disasters: conceptual model and empirical illustration. Issue 2 (7th October 2014) - L'Hermitte, Cécile; Tatham, Peter; Bowles, Marcus
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to use a theory-based approach to develop a new classification model for disasters that reflects their logistics implications, and to contextualise the findings by applying the model to a particular disaster situation. Design/methodology/approach – A widespread literature review was conducted in order to conceptualise the proposed disaster classification model and a case study (the 2011-2012 Somali food crisis) was used to provide a practical illustration and an initial validation of the conceptual approach. Findings – The new classification model proposes a set of four categories of disasters based on two generic dimensions, whilst simultaneously integrating five situational factors that reflect the impact of the external environment on the logistics operations. The case study confirms that this systemic approach is necessary since, from a logistics perspective, a disaster should be considered in its entirety and within its contextual environment. Research limitations/implications – Further research is needed to establish the operational characteristics of each disaster type in order to determine the applicability of business logistics practices to each scenario. In addition, this paper highlights the opportunity to validate or refine the model by using a more varied range of case studies. Originality/value – This paper proposes a new classification model for disasters based on their logistics implications and, by integrating the key environmental factors, it moves beyond the traditional 2×2 model found in the literature.